"Time that save lives" while waiting for ambulance in rural environments. (November 2021) - Nord-Ljungquist, Helena; Bohm, Katarina; Fridlund, Bengt; Elmqvist, Carina; Engström, Åsa
Highlights: In Sweden, firefighters perform 'While Waiting for the Ambulance' (WWFA) assignments. First aid is performed during WWFA assignments in long response time areas. In 95% of WWFA assignments, firefighters arrived 17 min before ambulance staff. In out-of-hospital cardiac arrests, firefighters arrived 19 min before ambulance staff. Deficiencies in documentation of WWFA assignments require methodological improvements. Abstract: Aim: Firefighters perform first aid before the ambulance arrives in areas with a long response time in Sweden; this is called 'While Waiting for the Ambulance' (WWFA). The aim was to describe WWFA assignments in rural environments, focusing on frequency, event time, actions and survival >30 days after cardiopulmonary resuscitation (CPR) was performed. Methods: Retrospective descriptive and comparative design. Results: Firefighters in the northern part of Sweden were involved in 518 WWFA assignments between 2012 and 2016. From alarm call until ambulance dispatch, median time was 2:20 min; for firefighters, nearly four minutes. Median dispatch time at out-of-hospital cardiac arrests (OHCA) (n = 52) was 1:40 min for ambulance and three minutes for firefighters. Maximal dispatch time was nearly 10 min for ambulance and 44 min for firefighters. Firefighters arrived first at the scene, after 17 min' median, for 95 % of assignments, while the ambulance took nearly twice the amount of time. In OHCA situations, time for firefighters was over 19 min versus ambulance at nearly twice the time. CPR was terminated by ambulance staff at 83% (n = 43) of 52 when firefighters performed prolonged CPR. Return to spontaneous circulation after OHCA was 17%, and 9% were alive after >30 days. Conclusion: The efficiency of incident time and utilisation rate for WWFA assignments can be increased for the benefit of affected persons, especially in OHCA.